Analysis Of Halal Destination Attributes And Service Quality On Muslim Tourism Interest In Bogor Regency - Roisiyatin, Roisiyatin; Anida Lutfiyah (FEBI UIN Sunan Kalijaga, 2025)
Bogor Regency with a Muslim population of approximately 87% of 5.6 million people, has potential for halal tourism development. This research aims to analyze the impact of halal destination attributes and service quality on Muslim tourist interest in Bogor Regency. This study uses a quantitative approach to the population of Bogor Regency residents, with a sample of 100 tourists. Data were collected through questionnaires with a Likert scale and analyzed using SPSS, tested for validity and reliability, classical assumption tests, multiple linear regression analysis, hypothesis testing, and R² determination test to measure the relationship between halal destination attributes and service quality Muslim tourist interest. The results showed that halal destination attributes (X1) were proven to have a partial effect on Muslim tourist interest with t-count 3.955 > t-table 1.984. Similarly, service quality (X2) partially affects Muslim tourist interest with t-count 3.435 > t-table 1.984. Simultaneous testing confirms that both independent variables together have a significant effect on Muslim tourist interest, with a coefficient of determination (R²) of 77.7%, while the remaining 22.3% is influenced by factors outside the research.